EDUCATION ON CARDIOPULMONARY RESUSCITATION MANAGEMENT ON THE KNOWLEDGE LEVEL OF RED CROSS YOUTH - Rofi'ah, Ika Ainur; Putra, Moch. Aldino Hidayat; Sukrisno, Adi (EZRA SCIENCE BULLETIN, 2024)
Cardiopulmonary Resuscitation (CPR) is a method for restoring the function of the respiratory and circulatory systems in patients experiencing sudden cardiac arrest or sudden cessation of breathing. CPR skills can be taught to anyone, including the general public, as cardiac arrest incidents can occur anytime and anywhere. The community service activities were carried out with a program providing education on CPR management on the knowledge level of students at Mojokerto City State 2 High School. Education was provided using a 2-method approach, namely the lecture method with material on the definition of CPR, indications for CPR, and CPR actions, and the CPR demonstration method using a mannequin. The sample for this community service activity consisted of 27 respondents, who were taken using total sampling techniques. The design used a pre-experimental and a one-group design pre-test-post-test approach. The instrument used a CPR knowledge questionnaire which was measured before and after education. The data analysis was the Wilcoxon test. The results of this community services activity showed that there was a significant difference before and after being given CPR education, knowledge in the CPR definition domain (p-value = 0.015; α <0.05), knowledge in the CPR indication domain (p-value = 0.000; α <0.05); knowledge in the CPR Action domain (p-value = 0.015; α <0.05). Education on cardiopulmonary resuscitation is essential, especially for the general public, as cardiac arrest can also occur outside of a hospital setting, thereby allowing individuals to assist.